Информационные технологии учебное пособие - Вичугова А. А. Анна Александровна; Вичугов В. Н. Владимир Николаевич; Дмитриева Е. А. Елена Анатольевна; Цапко Г. П. Геннадий Павлович (Томск, Изд-во ТПУ, 2012)
Заглавие с титульного экрана